Harmony to Tension: Understanding the Role of Religion in Social Conflict - Simamora, Izzatul Salsa Bila; Magfiroh, Ni’matul; Mujtahid, Mujtahid (Asian Journal of Philosophy and Religion, 2025)
Interreligious harmony has begun since the Abbasid era which continued with the Mughal period to the Sriwijaya kingdom in the 13th century. Some of the histories among the tense moments that have occurred at that time are such as the crusades, the Protestant Reformation, the division of India, and the Rwandan genocide. The purpose of this article is to provide readers with an overview of how to understand the role of religion in society. Then this article also provides readers with an overview of what are the factors that cause conflicts in the political and economic fields. And this article also provides an overview to readers about things that can affect the social and economic structure of society. The research method used in this article is the library research method, where the method is used by looking for sources in the form of books, journals, and other scientific works to be used as reference materials or references in this article. This article provides insight into the role of religion in shaping social identities and values, the factors that cause conflict, and its impact on social and economic structures.